2021
DOI: 10.1111/nyas.14656
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine modulations of reward‐driven music memory consolidation

Abstract: Music listening provides one of the most significant abstract rewards for humans because hearing music activates the dopaminergic mesolimbic system. Given the strong link between reward, dopamine, and memory, we aimed here to investigate the hypothesis that dopamine‐dependent musical reward can drive memory improvements. Twenty‐nine healthy participants of both sexes provided reward ratings of unfamiliar musical excerpts that had to be remembered following a consolidation period under three separate conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 68 publications
3
30
0
1
Order By: Relevance
“…Other studies have also reported improvements in cognitive function, as well as quality of life and depressive symptoms in patients with dementia and Alzheimer's disease 108,109 . Crucially, several studies have shown that musical reward and its different facets can predict music‐related benefits on cognition and well‐being 110–114 . A better characterization of subjects’ relationship with music by means of the eBMRQ might help, therefore, to predict the effectiveness of music‐based treatments at an individual level.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported improvements in cognitive function, as well as quality of life and depressive symptoms in patients with dementia and Alzheimer's disease 108,109 . Crucially, several studies have shown that musical reward and its different facets can predict music‐related benefits on cognition and well‐being 110–114 . A better characterization of subjects’ relationship with music by means of the eBMRQ might help, therefore, to predict the effectiveness of music‐based treatments at an individual level.…”
Section: Discussionmentioning
confidence: 99%
“…In study 2, 22 we investigated the neurochemical brain mechanisms underpinning such music‐pleasure‐driven effect on memory. By employing the same paradigm and material of study 1, we conducted a double‐blind, within‐subject pharmacological intervention.…”
Section: From Pleasure To Memory: Experimental Evidencementioning
confidence: 99%
“…of R responses probability), confirmed under placebo (gray solid line) and maintained under levodopa (green dashed line), was disrupted under risperidone (red dotted line). Panel adapted from Ref 22…”
mentioning
confidence: 99%
“…The overall score represents the general sensitivity to musical reward. [58][59][60][61] The study met the local ethical rules as laid out in French law concerning noninvasive protocols involving healthy participants and was classified as an observational study outside the scope of the Jardé law (Article R1121-1 of the French Law Code of Public Health amended by decree n°2017-884 of May 2017). It was submitted to the Ethics Committee CPP Est II, which exempted the study from the full ethics review process.…”
Section: Participantsmentioning
confidence: 99%